2020
DOI: 10.1155/2020/6782072
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Aortic Scaffold Alleviates H2O2-Induced Inflammation and Apoptosis in CD34+ Progenitor Cells While Driving Neovasculogenesis

Abstract: Bone marrow-derived stem/progenitor cells have been utilized for cardiac or vascular repair after ischemic injury, but they are subject to apoptosis and immune rejection in the ischemic site. Multiple scaffolds were used as delivery tools to transplant stem/ progenitor cells; however, these scaffolds did not show intrinsically antiapoptotic or anti-inflammatory properties. Decellularized aortic scaffolds that facilitate cell delivery and tissue repair were prepared by removing cells of patient-derived aortic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…On the other hand, some chemokines (GROα, PF4, NAP2, and RANTES) are considered to be important components of proinflammatory mediators and to interfere with the process of tissue regeneration [ [47] , [48] , [49] ]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some chemokines (GROα, PF4, NAP2, and RANTES) are considered to be important components of proinflammatory mediators and to interfere with the process of tissue regeneration [ [47] , [48] , [49] ]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is known to contribute to various cardiovascular diseases, including heart failure, myocardial infarct, and reperfusion injury [ 35 , 36 ]. Previous research has also shown that cardiac hypertrophy is related to a reduced cell number due to enhanced apoptosis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then the extracellular scaffolds inoculated with bone marrow progenitor cells were placed in different concentrations of hydrogen peroxide and found to have good antiapoptotic properties. 213 Walawalkar et al used chemicals and enzymes to decellularize the bovine aorta. The results showed that compared with other scaffolds, large diameter aortic ECM scaffolds could not only be prepared but also reendothelialized.…”
Section: The Application Of Decellularized Scaffolds In Tissue Engine...mentioning
confidence: 99%
“…Gao et al successfully prepared a decellularized aortic stent, which was used as the delivery carrier of bone marrow progenitor cells. Then the extracellular scaffolds inoculated with bone marrow progenitor cells were placed in different concentrations of hydrogen peroxide and found to have good antiapoptotic properties . Walawalkar et al used chemicals and enzymes to decellularize the bovine aorta.…”
Section: The Application Of Decellularized Scaffolds In Tissue Engine...mentioning
confidence: 99%